2002
DOI: 10.1080/11250000209356433
|View full text |Cite
|
Sign up to set email alerts
|

High mortality rate in a re‐introduced grey partridge population in central Italy

Abstract: A radio-tracking study was carried out on a re-introduced population of grey partridges in a 10.6-km 2 study area located in central Italy, in order to assess mortality rate and to evaluate the feasibility of carrying out large scale re-introductions of the species. Thirty-nine grey partridges were caught by live-traps during winter 2000 and equipped with backpack radio-transmitter. All released birds were offspring of partridges re-introduced previously on the study area and no significant differences were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 15 publications
0
29
2
Order By: Relevance
“…Negative effects may be caused by: 1) decreasing breeding success of wild birds that pair with reared birds (Rands & Hayward 1987), 2) attracting predators (Kenward 1981, Robertson 1988) and enhancing their interest in catching galliforms instead of other prey (Mueller 1971, Costantini et al 2005); however, DeVos & Speake (1995) did not find increased mortality of wild bobwhites after the release of artificially reared birds, 3) degrading genetics (Sage et al 2001, Ford 2002, Meriggi et al 2002, 4) genetic pollution (Barbanera et al 2007, Barilani et al 2007, Puigcerver et al 2007, and 5) increasing prevalence of parasites (Milla´n et al 2004, Villanua et al 2008. The use of medication in reared stocks may leave birds immunologically vulnerable when challenged by pathogens in the wild (Dowell 1992).…”
Section: The Aims Of Release and Choice Of Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative effects may be caused by: 1) decreasing breeding success of wild birds that pair with reared birds (Rands & Hayward 1987), 2) attracting predators (Kenward 1981, Robertson 1988) and enhancing their interest in catching galliforms instead of other prey (Mueller 1971, Costantini et al 2005); however, DeVos & Speake (1995) did not find increased mortality of wild bobwhites after the release of artificially reared birds, 3) degrading genetics (Sage et al 2001, Ford 2002, Meriggi et al 2002, 4) genetic pollution (Barbanera et al 2007, Barilani et al 2007, Puigcerver et al 2007, and 5) increasing prevalence of parasites (Milla´n et al 2004, Villanua et al 2008. The use of medication in reared stocks may leave birds immunologically vulnerable when challenged by pathogens in the wild (Dowell 1992).…”
Section: The Aims Of Release and Choice Of Techniquesmentioning
confidence: 99%
“…Moreover, the offspring of artificially reared galliforms that hatched in the wild have inferior survival and reproduction than truly wild birds (Woodburn 2001, Meriggi et al 2002. Dowell (1990a) released 8-9 week old grey partridges from natural, semi-natural (with hens) and artificial rearing.…”
Section: Galliforms After Releasementioning
confidence: 99%
“…Therefore, we assumed that these individuals had died. Previous studies have also found low survival rates in released partridges and most argued that, even if released birds survived to reach sexual maturity, their reproductive success would be very low (Putaala and Hissa, 1998;Meriggi et al, 2002;Duarte et al, 2011;Rymesova et al, 2013). This provides further support for rejecting stock enhancement as a tool to protect partridge populations.…”
Section: Discussionmentioning
confidence: 86%
“…Putaala and Hissa (1998) claim that released birds can only minimally contribute to the wild population due to their low survival and reproduction rates. Rymesova et al (2013), for example, recorded a mean lifespan of 14 ± 1.89 weeks with a minimum of 1 day and maximum of 78 days for 75 released partridges, while Meriggi et al (2002) reported 36.7 ± 6.0 weeks (min: 3 days, max: 94 days).…”
Section: Discussionmentioning
confidence: 99%
“…The European populations of Grey partridge (Perdix perdix Linnaeus 1758) declined from mid-1950s onwards with the reduction and the marked fragmentation of their historical range, especially along the range boundaries (Potts 1986;Potts and Aebischer 1994;Putaala and Hissa 1998;Meriggi et al 2002;Aebischer and Ewald 2004;De Leo et al 2004;Panek 2005;Meriggi et al 2007). Population decreases occurred to such an extent that the species was considered threatened and vulnerable and was classified in the list of the Species of European Conservation Concern in the third category (i.e.…”
Section: Introductionmentioning
confidence: 99%